"Humanizing intensive care: A scoping review (HumanIC)". (March 2022) - Kvande, Monica Evelyn; Angel, Sanne; Højager Nielsen, Anne
Significant scientific and technological advances in intensive care have been made. However, patients in the intensive care unit may experience discomfort, loss of control, and surreal experiences. This has generated relevant debates about how to humanize the intensive care units and whether humanization is necessary at all. This paper aimed to explore how humanizing intensive care is described in the literature. A scoping review was performed. Studies published between 01.01.1999 and 02.03.2020 were identified in the CINAHL, Embase, PubMed, and Scopus databases. After removing 185 duplicates, 363 papers were screened by title and abstract. Full-text screening of 116 papers led to the inclusion of 68 papers in the review based on the inclusion criteria; these papers mentioned humanizing or dehumanizing intensive care in the title or abstract. Humanizing care was defined as holistic care, as a general attitude of professionals toward patients and relatives and an organizational ideal encompassing all subjects of the healthcare system. Technology was considered an integral component of intensive care that must be balanced with caring for the patient as a whole and autonomous person. This holistic view of patients and relatives could ameliorate the negative effects of technology. There were geographical differences and the large number of studies from Spain and Brazil reflect the growing interest in humanizing intensive care in these particular countries. In conclusion, a more holistic approach with a greater emphasis on the individual patient, relatives, and social context is the foundation for humanizing intensive care, as reflected in the attitudes of nurses and other healthcare professionals. Demands for mastering technology may dominate nurses' attention toward patients and relatives; therefore, humanized intensive care requires a holistic attitude from health professionals and organizations toward patients and relatives. Healthcare organizations, society, and regulatory frameworks demanding humanized intensive care may enforce humanized intensive care.